2010
DOI: 10.1002/pat.1825
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of semifluorinated organo‐soluble new aromatic polyamides

Abstract: A series of organo‐soluble new polyamides were synthesized by the direct polycondensation of different semifluorinated aromatic diamines, namely 4,4‐bis[3'‐trifluoromethyl‐4'(4“‐amino benzoxy)benzyl]biphenyl; 4,4”‐bis(aminophenoxy)‐3'3“‐trifluoromethyl terphenyl; 1,3‐bis[3'‐trifluoromethyl‐4'(4”‐amino benzoxy)benzyl]benzene; 2,6‐bis(3'‐trifluoromethyl‐p‐aminobiphenyl ether)pyridine; and 2,5‐bis(3'‐trifluoromethyl‐p‐aminobiphenyl ether)thiophene with 5‐t‐butyl‐isophthalic acid. The polymers were fully character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…One of the common approaches for increasing solubility and processability of aramids without much sacrificing their high thermal stability is the introduction of bulky, packing‐disruptive groups into the polymer backbone . Introduction of trifluoromethyl (CF 3 ) groups into aramids has been one of the most widely used strategies for structural modification leading to substantial solubility enhancement . It has also been demonstrated that aramids containing three‐dimensional, propeller‐shaped triphenylamine (TPA) unit are amorphous, have good solubility in organic solvents and good film‐forming capability, and exhibit high thermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…One of the common approaches for increasing solubility and processability of aramids without much sacrificing their high thermal stability is the introduction of bulky, packing‐disruptive groups into the polymer backbone . Introduction of trifluoromethyl (CF 3 ) groups into aramids has been one of the most widely used strategies for structural modification leading to substantial solubility enhancement . It has also been demonstrated that aramids containing three‐dimensional, propeller‐shaped triphenylamine (TPA) unit are amorphous, have good solubility in organic solvents and good film‐forming capability, and exhibit high thermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…CFPA‐POSS had a lower dielectric constant than that of the other polyamides because of the presence of hexafluoroisopropylidene group. Such type of results could be ascribed the increase in the free volume reduction in chain–chain interaction in fluorinated nanocomposites [23,24]. It was observed that the polyamides containing bulky POSS and fluoro groups could effectively decrease dielectric constants of the polyamides.…”
Section: Resultsmentioning
confidence: 99%
“…All these PAs (Figure 4.7) showed good thermal stability (T d,10% = 409-475 °C) under air. It was observed that the polymer (PA A-xiii) containing quadriphenyl moiety showed higher tensile strength and higher elongation at break compared to the polymer containing terphenyl moieties (PA A-xi) [47,48]. The PA A-xiii exhibited the highest T g value (261 °C) in the series, which could be explained on the basis of the presence of a rigid quadriphenyl unit in the polymer backbone.…”
Section: Fluorinated Poly(ether Amide)smentioning
confidence: 98%
“…The effect of the heterocyclic moiety and the catenation angle on the poly(ether amide)s was also investigated [47]. It was observed that with the decrease in the catenation angle, the solubility of the polymers increased due to the inhibition in polymer chain packing.…”
Section: Fluorinated Poly(ether Amide)smentioning
confidence: 99%
See 1 more Smart Citation